The Contestation of Contemporary Islam: Conservative Islam versus Progressive Islam - Qodir, Zuly; Singh, Bilveer (UIN Sunan Kalijaga Yogyakarta, 2022)
This article analyzes the articulation of Islamic thought in the 2014 and 2019 General Elections in Indonesia, both of which were marked by efforts by progressive and conservative Muslims to dominate public spaces. Contestation was evident in these political discourses, with progressive Muslims advocating for moderatism, political ethics, and tolerance in narratives of inclusivism, pluralism, and tolerance while conservative Muslims disseminating extremism, the formalization of sharia law, and intolerance in narratives of exclusivism and homogenization. The analysis questions the continuity-discontinuity, motives, and actors of both progressive and conservative Muslim movements and investigates the challenges for progressive Muslims in disseminating their narratives in Indonesia. The result argues that massive religious organizations in Indonesia articulate, internalize, and institutionalize progressive thought within their organizations and educational institutions. This article encourages progressive Muslims to reckon with and countermeasure conservativism among religious and political elites whose narratives exploit religious sentiments for practical purposes.